2012
DOI: 10.3136/fstr.18.251
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Extractions of Brown Seaweeds and Analysis of Their Lipid Fraction in Methanol

Abstract: In this present study, fucoxanthin has been successfully extracted and purified from two species of Malaysian brown seaweeds, namely Sargassum binderi and S. duplicatum. The purity of the fucoxanthin obtained was > 99% as indicated by HPLC analysis. Both fucoxanthin content, and analysis of lipid fraction of the seaweeds in methanol showed that both samples contained a considerable amount of fucoxanthin and total lipids. The amount of fucoxanthin and total lipid farcation in methanol of S. duplicatum (1.01 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 27 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…In the past preparative thin layer chromatography (TLC) practices, solvents that were commonly used to isolate fucoxanthin in brown macroalgae (Hijikia fusiformis, Sargassum sp.) were diethyl ether and ethyl acetate [32,43]. However, this study found dichloromethane to have a better ability in concentrating fucoxanthin.…”
Section: Solvent Systemsmentioning
confidence: 68%
See 1 more Smart Citation
“…In the past preparative thin layer chromatography (TLC) practices, solvents that were commonly used to isolate fucoxanthin in brown macroalgae (Hijikia fusiformis, Sargassum sp.) were diethyl ether and ethyl acetate [32,43]. However, this study found dichloromethane to have a better ability in concentrating fucoxanthin.…”
Section: Solvent Systemsmentioning
confidence: 68%
“…The extractable yield was comparably higher than the methanolic extracts of the brown macroalgae, Sargassum polycystum (4.05%) [29] as well as commercial microalgae, Spirulina platensis (7.3%) [30]. Methanol is a very common solvent used in the extraction of antioxidant bioactives from algae [31,32] and herbs [33] alike. Solvents suitable for utilization within foods have been listed by various organizations, including the World Health Organization (www.who.int), the Food and Drug Administration (www.fda.gov) and the European Food Safety Authority (www.efsa.…”
Section: Extraction and Fractionation Yieldsmentioning
confidence: 99%
“…Nonetheless, many of the fucoxanthin‐containing health products commonly marketed as fat burners are mainly based on extracts obtained from brown seaweeds. Use of brown seaweeds as a source of bioactive natural products (especially fucoxanthin), however, has major shortcomings compared with microalgae, including slow growth, relatively large cultivation space, low biomass utilization efficiency, low fucoxanthin content (0.1–3.7 mg g –1 ), and relatively complex extraction procedure . Microalgae have been identified to be a more promising source of fucoxanthin and other potential beneficial compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Use of brown seaweeds as a source of bioactive natural products (especially fucoxanthin), however, has major shortcomings compared with microalgae, including slow growth, relatively large cultivation space, low biomass utilization efficiency, low fucoxanthin content (0.1-3.7 mg g -1 ), and relatively complex extraction procedure. [13][14][15] Microalgae have been identified to be a more promising source of fucoxanthin and other potential beneficial compounds. In 2017, a 3% fucoxanthin extract prepared from the microalga Phaeodactylurn tricornutum was approved by FDA to be used as a dietary ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Brown seaweed is characterized by natural brown color that derived from fucoxhanthin and natural thickener namely alginate. [9][10][11][12][13][14][15] Candy is one of favorite confectionery foods among people from a wide range of age. Jelly candy is characterized by a soft and chewy texture typically conferred by a gelatin or pectin-based gel.…”
Section: Introductionmentioning
confidence: 99%